School Administrators and Teachers’ Knowledge of Educational Laws: A Basis for Program Development and Intervention - Yllano, Amada C.; Voropaeva, Kseniia; Famerong, Jeremiah C. (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
A knowledge of education law is inevitable in running the school smoothly and has prime importance to all personnel in the institution, particularly to the school administrators and teachers. Understanding the legal implication of one’s duty and function, the school administrators and teachers will learn how to act in situations where due process of law requires. Past research has advocated for more and better school law training for educators and administrators, yet little significance has occurred. Hence, the school administrators' and teachers' knowledge of educational laws has been studied, including the basis for program development. The education law literacy of administrators and teachers of private schools and its association with their age, gender, educational background, teacher certification, length of experience, and exposure to education law were analyzed. A researcher-made survey instrument consisting of a 15-item education law test on students' and teachers' rights was utilized. A mixed-method quantitative-qualitative design was used. Results showed a poor overall literacy level of administrators and teachers on educational law. Moreover, there was a low association between education, law literacy, and law background. The results of this study serve as the basis for program development and intervention on educational law literacy among administrators and teachers. Keywords : education law literacy, school administrators, educators, student and teacher rights